Globally aggregated biodiversity data impact predictive and descriptive research - Dirk Steinke; Birgit Gemeinholzer; Enrique Martínez-Meyer; Daniel Noesgaard; Andrew Young; Dmitry Schigel (Proceedings of the National Academy of Sciences, 2025)
Here, we present an analysis of the growth and use of the Global Biodiversity Information Facility (GBIF) over the last 5 y. GBIF is the world’s largest data integrator for biodiversity information and plays a central role in research across the biodiversity and evolutionary science community. With the help of a comprehensive bibliographic dataset comprising 12,193 studies that used GBIF-mediated data, we demonstrate how the global scientific community utilizes the continuously fast-growing amount of open and Findable, Accessible, Interoperable, and Reusable biodiversity data in their research. Overall, more researchers engage with GBIF data, a potential consequence of the rising demands of more global environmental assessments, where GBIF-mediated data are being used as a key resource for biodiversity research. Studies utilizing species distribution modeling were most prevalent and data used for topics related to challenges of the Anthropocene (conservation, climate change, invasive, and pest species). More studies used observational data records, a category that also includes a substantial amount of citizen science data. Our data show that a thematic diversification of GBIF-using literature is accompanied by a rapid diversification of both the additional datasets that GBIF data are analyzed with, as well as the new analytical approaches taken by researchers. This emphasizes the growing importance of GBIF’s data infrastructure and services which support global sciences and reflect major shifts in applied science which dictate the need for GBIF and similar data infrastructures to evolve rapidly in order to maintain relevance for research.